Comparison of methods for the identification of microorganisms isolated from blood cultures - Monteiro, Aydir Cecï¿½lia Marinho [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Ferreira, Adriano Martison [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; Mondelli, Alessandro Lia [UNESP]; Bagagli, Eduardo [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza [UNESP] (Springer Nature, 2016)
Background: Bloodstream infections are responsible for thousands of deaths each year. The rapid identification of the microorganisms causing these infections permits correct therapeutic management that will improve the prognosis of the patient. In an attempt to reduce the time spent on this step, microorganism identification devices have been developed, including the VITEKï¿½ 2 system, which is currently used in routine clinical microbiology laboratories. Methods: This study evaluated the accuracy of the VITEKï¿½ 2 system in the identification of 400 microorganisms isolated from blood cultures and compared the results to those obtained with conventional phenotypic and genotypic methods. In parallel to the phenotypic identification methods, the DNA of these microorganisms was extracted directly from the blood culture bottles for genotypic identification by the polymerase chain reaction (PCR) and DNA sequencing. Results: The automated VITEKï¿½ 2 system correctly identified 94.7 % (379/400) of the isolates. The YST and GN cards resulted in 100 % correct identifications of yeasts (15/15) and Gram-negative bacilli (165/165), respectively. The GP card correctly identified 92.6 % (199/215) of Gram-positive cocci, while the ANC card was unable to correctly identify any Gram-positive bacilli (0/5). Conclusions: The performance of the VITEKï¿½ 2 system was considered acceptable and statistical analysis showed that the system is a suitable option for routine clinical microbiology laboratories to identify different microorganisms.
Keywords: Automated VITEKï¿½ 2 system; Blood culture; Genotypic identification; Phenotypic identification